Games, ideas and activities for primary science - Dabell, John. (Harlow, England : Longman, 2010)
This book aims to provide ready-made science lesson ideas that will considerably reduce the workload for many overburdened teachers. They can be easily adapted to suit varying levels of ability, and bring science to life. The structure of the book mirrors the QCA scheme of work.
Includes bibliographical references.
Keywords: Science -- Study and teaching (Primary) -- Activity programs